The Requirements of the Contemporary Labour Market for Professionals - Tetiana Balanovska; Barbara Wyrzykowska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article substantiates that the contemporary labour market with its flexibility, volatility, high innovation dynamics, as its main features, introduces new requirements for employees. The study analyses the Ukrainian population’s employment, in the rural areas, forestry and fishing, in particular. The study determines the problems of the insufficient level of satisfaction of the employers’ need in employees. The research sums up different scientific approaches to the expectation that employers have to professional specialists. It establishes that employers' requirements for future employees differ regarding their professional experience. The article explains the findings of the research assisting specialists to focus on the core knowledge concerning the practical aspect. The article provides analysis that refers to the set of personal qualities and abilities acting as factors of managers’ compliance with the demands of the contemporary labour market. The findings of the article single out the role and significance of logical thinking as a component of forming successful managers.